STATISTICAL SYNTHESIS OF FORECAST CHARACTERISTICS OF COMPLEX TECHNICAL SYSTEM BY TIME SERIES - N. A. Severcev; V. M. Balick; E. V. Balick (Научный вестник МГТУ ГА)
The article analyses the problem of building a medium-term forecast of the recovery trend in the average. We present a method of recovery trend in the form of a polynomial whose coefficients are determined by the inverse functions which are approximated by trigonometric polynomials. Also there are the conditions describing the process of constructing trend in this article.